Simple machines : wheels, levers, and pulleys - Adler, David A. (Holiday House, 2015)
Kids use simple machines every day without realizing it. Teeth are wedges and so are knives, forks, and thumbtacks. Many toys such as slides, which are inclined planes, and seesaws, which are levers, are also simple machines. Two appealing kids and their comical cat introduce levers, wheels, pulleys, inclined planes, and more, and explain how they work. This lively introduction to physics will get kids excited about how simple machines simplify our lives.